Modeling of the thermal properties of SARS-CoV-2 S-protein - Niu, Ziyuan; Hasegawa, Karin; Deng, Yuefan; Zhang, Ziji; Rafailovich, Miriam; Simon, Marcia; Zhang, Peng (Frontiers in Molecular Biosciences, 2022)
We calculate the thermal and conformational states of the spike glycoprotein (S-protein) of SARS-CoV-2 at seven temperatures ranging from 3℃ to 95℃ by all-atom molecular dynamics (MD) µs-scale simulations with the objectives to understand the structural variations on the temperatures and to determine the potential phase transition while trying to correlate such findings of the S-protein with the observed properties of the SARS-CoV2. Our simulations revealed the following thermal properties of the S-protein: (1) It is structurally stable at 3℃, agreeing with observations that the virus stays active for more than two weeks in the cold supply chain; (2) Its structure varies more significantly at temperature values of 60℃ to 80℃; (3) The sharpest structural variations occur near 60℃, signaling a plausible critical temperature nearby; (4) The maximum deviation of the receptor-binding domain at 37°C, corroborating the anecdotal observations that the virus is most infective at 37°C; (5) The in silico data agree with reported experiments of the SARS-CoV-2 survival times from weeks to seconds by our clustering approach analysis. Our MD simulations at µs scales demonstrated the S-protein’s thermodynamics of the critical states at around 60℃, and the stable and denatured states for temperatures below and above this value, respectively.